Prior Learning Assessment and Recognition (PLAR) in Canadian Universities - Belanger, Charles H.; Mount, Joan (Canadian Journal of Higher Education, 2017)
This study suggests that Prior Learning Assessment and Recognition (PLAR) is gaining legitimacy in the university setting because of the Government/ Industry/ Labour agenda to prepare the workforce for the twenty first century; because of growing emphasis on lifelong learning characterized by mature students, part-time studies, and modular programs; because of the increasing integration of colleges and universities; and because of the prospective students' conviction that learning outside the classroom should be validated. Quality assurance and administrative issues have still to be resolved. At the same time, however, PLAR is not yet an important ingredient of university culture.